ANALISIS PENGEMBANGAN OBYEK WISATA PEMANDIAN ALAM KARANG ANYAR, KECAMATAN GUNUNG MALIGAS, KABUPATEN SIMALUNGUN, PROVINSI SUMATERA UTARA - Novitasari Pardede; Muhdi Muhdi; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
Forest use is done by direct benefits (tangible) and indirect benefits (intangible). Indirect benefits (intangible) such as forest benefits in the form of immaterial or utilization of environmental services like nature which refers to the ecological principle can be used as an alternative to support long-term development of the country. One of the benefits that can be gained is the development of natural forest areas for ecotourism. This study aims to: (1) analyzing the potential attraction to attraction Nature Baths Karang Anyar; (2) to analyze the problems of nature tourism development strategy in the region SWOT attractions Nature Baths Karang Anyar. Sampling was done by purposive sampling techniques for the respondents and random techniques to the public. Objects and appeal that has been obtained and analyzed in accordance with the criteria in the Guidelines scoring Regional Operations Analysis Objects and Attractiveness Director General of Nature Protection and Nature Conservation in 2003 in accordance with a predetermined value for each criterion. Nature Baths Karang Anyar has potential natural attractions should be developed with a percentage of 73,88%. In the SWOT analysis, are in quadrant I, which indicates that this is a tourist area in a favorable situation. Keywords: Karang Anyar Nature Baths, Ecotourisme, development analisys, Gunung Maligas.